EVALUATION OF THE IMPLEMENTATION OF CHARACTER EDUCATION STRENGTHENING IN THE CONTEXT OF GUIDANCE AND COUNSELING IN BOARDING SCHOOLS - Dwi Cahyaningrum, Vesti; Hidayah, Nur; Hotifah, Yuliati; Da'i, Mohamad (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Strengthening Character Education (PPK) aims to shape students with strong character in addition to academic achievement. The implementation of PPK in the context of guidance and counseling in boarding school-based schools is very important to optimize the moral and social development of students. This study aims to evaluate the effectiveness of PPK implementation in guidance and counseling services at SMA Plus Al Fatimah Bojonegoro, a boarding school-based institution. This research uses a quantitative method with data collection through questionnaires distributed to 100 students, as well as questionnaires for guidance counselors and the school principal. The research results show that 37.5% of students strongly agree, 39% agree, 16.5% somewhat agree, 5% disagree, and 2.5% strongly disagree regarding the effectiveness of PPK in shaping their character. Meanwhile, 59% of guidance counselors and principals strongly agree, 31% agree, and 10% somewhat agree with the effectiveness of this program. No respondents disagreed or strongly disagreed. The conclusion of this study shows that the implementation of PPK at SMA Plus Al Fatimah Bojonegoro is generally effective, but there are still challenges in the consistency of implementation and student involvement. Recommendations are given to enhance the synergy between teachers, counselors, and school authorities to strengthen the implementation of this program.